The Disabled Body in Julie Taymor’s Frida - Micki Nyman (Disability Studies Quarterly, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Director Julie Taymor says that her choice to direct Frida (2002) was made, in part, by the “prospect of striking a balance between the realism of a period piece set in the Twenties, Thirties and Forties and the interior landscape of this woman’s mind” (Bosley 1). To convey to the audience a combined sense of Frida Kahlo’s subjectivity, artistry and biography, Taymor employs digitally altered scenes to recreate her paintings which then come to life within the narrative. Taymor also suggests a recurrent theme in Kahlo’s oeuvre, the permeability of death and life, while layering Frida’s inner realities, her maimed body, and aspects of her culture, both modern and traditional. Ultimately, Taymor’s focus on Frida’s disabled body helps film audiences understand the complexity of Kahlo’s life journey, one that continues to be constructed even after her death.
Keywords: disability; body; subjectivity; Frida Kahlo; biopic; disabled body; Julie Taymor; film; biography